Effects of high-intensity interval training in men soccer player's physical fitness: A systematic review with meta-analysis of randomized-controlled and non-controlled trials. Issue 11 (3rd June 2021) - Manuel Clemente, Filipe; Ramirez-Campillo, Rodrigo; Nakamura, Fábio Yuzo; Sarmento, Hugo
ABSTRACT: This systematic review with meta-analysis (SRMA) was conducted to assess the effects of high-intensity interval training (HIIT) programmes on men soccer players' aerobic fitness (maximal oxygen uptake and aerobic performance), repeated sprint ability (RSA), vertical jump height (VJH), and linear sprinting time (ST). An electronic search yielded 1, 714 articles, 33 of which were included in the present study. Meta-analyses revealed significant benefits of HIIT compared to controls in maximal oxygen uptake (p = 0.018), AP (p = 0.041), and RSA (p = 0.049). No significant effects were found in terms of ST (p = 0.080). The meta-analyses of non-controlled studies revealed significant improvements after HIIT in maximal oxygen uptake (p = 0.001), AP (p = 0.007), RSA (p = 0.001), and ST (p < 0.001). However, no significant improvements in VHJ were found (p = 0.063). Furthermore, no significant differences were found in sub-group analysis (comparisons between HIIT types). In conclusion, HIIT is effective for improving maximal oxygen uptake, AP, and RSA regardless of the HIIT type. For VHJ and ST outcomes, it seems reasonable to complement the HIIT since it might not be enough to achieve significant changes.